Engaged archaeology in the southwestern United States and northwestern Mexico - Hays-Gilpin, Kelley A., editor; Herr, Sarah A., editor; Lyons, Patrick D., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2021)
Organized around the theme of "interdisciplinary perspectives," the authors identify current and near-future trends in archaeological practice in the Southwest US and Northwestern Mexico, including repatriation, community engagement, and cross-disciplinary approaches, and focuses on Native American archaeologists and their communities, research, collaborations, and interests.--Provided by publisher.
Engaged archaeology today / Sarah A. Herr, Patrick D. Lyons, and Kelley A. Hays-Gilpin -- Research in the service of repatriation in the Southwest / T. J. Ferguson -- Modeling cultural interactions and expanding traditional histories: research and NAGPRA compliance on the Coconino National Forest / Peter J. Pilles, Jr., Kimberly Spurr, and Leigh J. Kuwanwisiwma -- Reassessing the burial assemblages of Nuvakwetaqa, Chavez Pass, Arizona / Arleyn Simon, Christopher Caseldine, Sarah Striker, Christopher Grivas, Neysa Grider-Potter, and Darsita R. North -- Bioarchaeological research resulting from NAGPRA compliance efforts / Debra L. Martin -- Repatriation and the evolution of osteological practice / John A. McClelland -- Identity and cultural affinity in the Alameda-Stone Cemetery, Tucson, Arizona: bioarchaeological, contextual, and archival evidence / Michael Heilen and Teresita Majewski -- Creating a safe space for Western Apache repatriation: working with native communities to better understand published and unpublished documentary sources / Vernelda Grant and Cécile R. Ganteaume -- Why does repatriation matter? / Chip Colwell -- Kiowa-Tanoan kin terms and ancestral Pueblo social organization / Patrick Cruz and Scott Ortman -- Research at the intersection of archaeology and ethnology: reviving the direct historical approach / John A. Ware -- Archaeology as ethnology (and vice versa): Puebloan variations / Peter M. Whiteley -- Reviving the direct historical approach on the western margins of the Southwest: the evolution of kinship terminologies in the Yuman languages / Jane H. Hill -- Grand ideas: from engaged ethnology to informed archaeology / Kelley Hays-Gilpin -- Connecting with the past through Hopi ethnobotanical collections / Lisa C. Young and Susan Sekaquaptewa -- The landscape of Navajo identities / Kerry F. Thompson -- Experimental replication and technological comparison of turquoise manufacturing techniques in Mesoamerica, northern Mexico, and the southwestern United States / Emiliano Ricardo Melgar Tísoc -- Archaeometric analysis of prehispanic turquoise objects from Chalchihuites, Zacatecas, México / Guillermo Córdova Tello and Estela Martínez Mora.
Keywords: Cultural property -- Repatriation -- Southwest, New; Cultural property -- Protection -- Southwest, New; Indians of North America -- Southwest, New; Indians of North America -- Mexico, North; Archaeometry -- Southwest, New; Archaeometry -- Mexico, North; Ethnoarchaeology; Southwest, New -- Antiquities; Mexico, North -- Antiquities